2016
DOI: 10.1128/msphere.00121-16
|View full text |Cite
|
Sign up to set email alerts
|

Separate F-Type Plasmids Have Shaped the Evolution of the H 30 Subclone of Escherichia coli Sequence Type 131

Abstract: A clonal lineage of Escherichia coli known as ST131 has emerged as a dominating strain type causing extraintestinal infections in humans. The evolutionary history of ST131 E. coli is now well understood. However, the role of plasmids in ST131’s evolutionary history is poorly defined. This study utilized real-time, single-molecule sequencing to compare plasmids from various current and historical lineages of ST131. From this work, it was determined that a series of plasmid gains, losses, and recombinational eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(144 citation statements)
references
References 35 publications
11
118
1
Order By: Relevance
“…The SNV-based phylogeny showed differentiation of our ST131 strains into the previously described H30R1 and H30Rx clades (11)(12)(13) , demonstrating fixation and ongoing evolution of specific plasmids within these separate but closely related sublineages (15). Our data extend these findings to community hospital source ST131 isolates.…”
Section: 008supporting
confidence: 77%
See 1 more Smart Citation
“…The SNV-based phylogeny showed differentiation of our ST131 strains into the previously described H30R1 and H30Rx clades (11)(12)(13) , demonstrating fixation and ongoing evolution of specific plasmids within these separate but closely related sublineages (15). Our data extend these findings to community hospital source ST131 isolates.…”
Section: 008supporting
confidence: 77%
“…For E. coli ST131 isolates, subclones H30R (ciprofloxacin resistant; fimH allele 30), H30Rx (a CTX-M-15-associated clonal subset within H30R), and H30R1 (a sister clade to H30Rx within H30R) were classified as described previously (11,15). H30Rx was defined based on a specific SNV, ybbW G723A, as identified by BLASTn (http://blast.ncbi.nlm.nih.gov/Blast.cgi) (19).…”
Section: Methodsmentioning
confidence: 99%
“…IncF plasmids are the most abundant plasmid type found in enterobacteria (de Toro et al, 2014). They are key to the generation and spread of clonal groups like E. coli ST-131 (Lanza et al, 2014; Johnson et al, 2016), and they are fundamental vehicles for the spread of antibiotic resistances (de Been et al, 2014). We hope that analysis using comparative genomics, like the one presented here, will help unraveling the causes behind the prevalence and evolutionary success of IncF plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…Besides their common mating apparatus, F-like plasmids appear to be functionally diverse. For instance, they may encode different replication and partition systems (Ogura and Hiraga, 1983; Gerdes and Molin, 1986), and a wide diversity of cargo genes (Lanza et al, 2014; Johnson et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The evolutionary history of clone ST131 revealed that before the emergence and dissemination of subclone H 30 (also called clade C), the ST131 population consisted of mostly two subclones called H 22 (clade B) and H 41 (clade A), with subclone H 22 comprised of mostly fluoroquinolone-susceptible isolates [35]. It also revealed that subclone H 22 was the precursor of subclone H 30 and that separate F-type plasmids have shaped the evolution of subclone H 30 [2, 3, 5, 6]. The most recent ST131 E. coli phylogenetic reconstruction carried out by Ben Zakour et al using 3779 non-recombinant single nucleotide polymorphisms (SNP) found in the high quality genomes of 172 clade B and C strains, identified five B subclades, for which the independent evolutionary trajectories are characterized by successive insertions and a recombination from ancestral H 22 (subclade B1) [7].…”
Section: Introductionmentioning
confidence: 99%